Tantangan Pengembangan Kurikulum Fikih Pada Madrasah Diniyah Takmiliyah Miftahussa’adah Desa Banjarwinangun Petanahan - Wahyuningsih, Wahyuningsih; Irodati, Fibriyan (IAINU Kebumen, 2025)
This study aims to identify, analyze, and understand in depth the challenges in the development of the Islamic jurisprudence curriculum faced by Madrasah Diniyah Takniliyah Miftahussa'adah, Banjarwinangun Village, Petanahan District, Kebumen Regency. The research method used is qualitative with a case study approach carried out by taking data sources from the principal, teachers and students of MDT Miftahussa'adah through purposive sampling. Data were collected through in-depth interviews, validated by source triangulation, then analyzed interactively. The results of the study indicate that MDT Miftahussa'adah faces challenges in learning methods that are not yet innovative, teacher and student discipline, student interest and motivation in learning, facilities and infrastructure, and curriculum factors. These various challenges require innovative strategies so that Islamic religious education remains relevant and attractive to the younger generation.